INFLUÊNCIA DOS FENÔMENOS EL NIÑO/LA NIÑA NA VEGETAÇÃO DO BIOMA MATA ATLÂNTICA - Carvalho, Rita de Cássia Freire (2020)
The Atlantic Forest is known worldwide as one of the most important biomes in Brazil, rich in biodiversity and also one of the most endangered on the planet. Weather events such as El Niño and La Niña can affect the weather conditions in some regions of t